2022
DOI: 10.5194/acp-22-4853-2022
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the significant increase in ozone during COVID-19 in a typical urban city of China

Abstract: Abstract. The outbreak of COVID-19 promoted strict restrictions to human activities in China, which led to a dramatic decrease in most air pollutant concentrations (e.g., PM2.5, PM10, NOx, SO2 and CO). However, an obvious increase in ozone (O3) concentrations was found during the lockdown period in most urban areas of China. In this study, we conducted field measurements targeting ozone and its key precursors by utilizing a novel proton transfer reaction time-of-flight mass spectrometer (PTR-TOF-MS) in Changzh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…It was supposed that the solar radiation in winter was much lower than that in summer and autumn (Jin et al, 2005;Tang et al, 2010). However, AOC in our study was significantly higher than that during the same period in Changzhou (Zhang et al, 2022a). As shown in Figure 5, the contribution of OH to AOC reached 85% during the whole study period, and thus the higher OH concentration in Tangshan was responsible for the higher AOC compared with Changzhou.…”
Section: Aoc and Radical Chemistry After Covid-19 Lockdownmentioning
confidence: 47%
“…It was supposed that the solar radiation in winter was much lower than that in summer and autumn (Jin et al, 2005;Tang et al, 2010). However, AOC in our study was significantly higher than that during the same period in Changzhou (Zhang et al, 2022a). As shown in Figure 5, the contribution of OH to AOC reached 85% during the whole study period, and thus the higher OH concentration in Tangshan was responsible for the higher AOC compared with Changzhou.…”
Section: Aoc and Radical Chemistry After Covid-19 Lockdownmentioning
confidence: 47%
“…In addition, the ambient concentration and chemistry are largely regulated via meteorological factors (wind speed, wind direction, relative humidity, planetary boundary layer or mixing height) of the regions (Kumar and Yadav 2016 ; Karle et al 2021 ). The study conducted over the Yangtze River Delta (YRD) city cluster of China to observe the effect of source and meteorology on ozone formation reported 5.1 ppbv contribution for ozone formation regulated via precursor mediated while 0.5 ppbv contribution via meteorological factor (Zhang et al 2021a ). The other study carried out in Handan and the industrial city in China suggests that ozone formation in the ambient atmosphere is a combined effect of reduction in source and meteorology (Yao et al 2021 ).…”
Section: Factors Affecting Air Pollution (Indoor and Outdoor)mentioning
confidence: 99%
“…The variation in pollutants reduction during the lockdown period could be due to variations in geographical location, meteorological conditions, and atmospheric chemistry. Recently, it has been observed that ozone concentration level in different cities increases during the lockdown period due to alteration in atmospheric chemistry and emission pattern (Zoran et al 2020 ; Zheng et al 2020 ; Zhang et al 2021a ). The tropospheric ozone formation is largely governed via NO x -VOC S -HO x cycle in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Control of O 3 pollution is challenging, partly due to the non-linear connections between O 3 and its precursors, such as nitrogen oxides (NOx) and volatile organic compounds (VOCs) ( de Foy et al, 2020 ; Zavala et al, 2020 ). Based on the reactivity of O 3 to its precursors, the photochemical regime of O 3 formation can be classified into categories such as NO x -limited and VOC-limited ( Zhang et al, 2022 ). Due to high NO x emissions, dominant O 3 formation regime in urban areas of China is believed to be VOC-limited ( Ding et al, 2013 ; Shao et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%